Analysis of a novel subway station structure to mitigate damages induced by normal faulting. Issue 136 (September 2020) - Yao, Chaofan; Yan, Qixiang; Sun, Minghui; Zhang, Junchen; He, Chuan
Abstract: Underground structures are more vulnerable to faulting than earthquake shaking. However, there are no effective mitigation measures for the damages of underground structures subjected to normal faulting. This study proposes a novel structure for new subway stations to mitigate the normal fault induced damages. The novel subway station consists of a rectangular cross-section and two rigid diaphragm walls. The diaphragm walls are made of reinforced concrete, connecting with the bottom corners of the structure. A series of analyses was conducted by finite elements, which had thoroughly validated in previous studies. The results show that the responses of the novel structure depend on fault throw, its location relative to the rupture, soil depth, burial depth, and the length of diaphragm walls. The presence of diaphragm walls substantially reduces the structure rotation in two ways: (1) obtaining skin friction from surrounding soil to conquer the rigid body rotation, and (2) restraining differential soil displacements underneath the bottom slab. Highlights: The novel structure can substantially reduce the structure rotation. The structure behaviors depend on wall length, relative location, and soil depth. The length of the diaphragm wall is a key design factor.